Класифікація сучасних садових груп троянд за способом їх практичного використання - Tkachuk, О.О. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2004)
On the basis of analysis of garden rose existing classifications the unified scheme that is more close to the modern practice is suggested.